Hubungan Motivasi Belajar dan Media Pembelajaran Audio Visual terhadap Minat Belajar Siswa (International Forum of Researchers and Lecturers, 2023)
This research was conducted with the aim of knowing the relationship between learning motivation and audio-visual learning media on students' learning interest at SDN 1 Siluman. This study uses a quantitative approach and the type of research chosen is correlation research. The population is all grade VI students at SDN 1 Siluman for the academic year 2023/2024 with a total of 54 students. The sample used is saturated sampling, so the entire population is sampled in this study. Data collection techniques through questionnaires. Data analysis techniques through correlation testing. Based on the research results, it can be seen that there is a relationship between learning motivation and students' interest in learning with a correlation coefficient of 0.719, so it can be combined based on the interpretation correlation coefficient as a strong relationship. There is a relationship between audio-visual learning media and student learning interest with a correlation coefficient of 0.696, so it can be classified based on the interpretation correlation coefficient as a strong relationship. There is a relationship between audio-visual learning media and learning motivation with a correlation coefficient of 0.932, so it can be categorized based on the interpretation of the correlation coefficient as a very strong relationship. Based on this research, educators can increase student motivation and interest in learning with the use of audio-visual media.